Penerapan Model Pembelajaran Quick Onthedraw Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika - Muamalah, Harisatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2020)
This study aims to determine: (1) the process of applying the quick on the draw learning model (2) increasing the ability to understand students' mathematical concepts after the implementation of the quick on the draw learning model. The research subjects were students of class VIII B AL-BADRI SMP, totaling 42 students. This research is classified as Classroom Action Research with a qualitative approach. This research was conducted in two cycles, in this study, students were said to be complete if they met the completeness ≥70%. Based on the analysis of research data the percentage of learning outcomes in the first cycle is 69% and the results of the second cycle test is 100%. Whereas Based on the results of the analysis of student responses to the quick on the draw learning model in the material relations and functions of class VIII B in SMP AL-BADRI has a very good response to the percentage of student responses 94.59%.